Pictorial Representations of Occupational Accidents in the Nineteenth Century: An Analysis from the Perspective of Risk Prevention - Rodríguez Elizalde, Rubén (Journal of Ecohumanism, 2025)
Workplace accidents were a pervasive reality during the 19th century, particularly in the wake of the Industrial Revolution, when labor conditions were harsh, and safety measures were virtually nonexistent. Amid this context, painting emerged as a powerful medium for documenting the struggles of the working class, offering both a visual testimony of occupational hazards and a reflection of evolving social awareness.This study examines a selection of Spanish 19th-century paintings through the lens of occupational risk prevention. Using an iconographic and contextual analysis, key works from costumbrismo and social realism are explored. These artworks not only depict workplace accidents but also expose the precarious conditions in which workers operated, highlighting the absence of protective measures and the profound human cost of industrial labor.The analysis is structured around four key themes: the visual representation of workplace accidents, the physical environment and safety conditions, societal responses to labor-related tragedies, and the evolution of working-class iconography in 19th-century painting. Through this approach, the study establishes a dialogue between past labor struggles and modern occupational health and safety principles, providing insight into how these historical representations resonate with contemporary concerns.Beyond their artistic and documentary significance, these paintings reveal how workplace accidents were perceived in a society undergoing profound transformation. As labor movements gained momentum and industrialization reshaped the economic landscape, art played a crucial role in shaping the collective memory of labor and raising awareness about occupational risks. This study underscores the enduring relevance of these visual narratives and their capacity to inform current debates on workplace safety and workers' rights.